Global Research Priorities for Holistic Integration of Water and Power Systems - Rebecca O'Neil; Konstantinos Oikonomou; Vince Tidwell; Nathalie Voisin; Jessica Kerby; Z. Jason Hou; Masood Parvania; Ali T. Al-Awami; Mathaios Panteli; Steven A. Conrad; Ted K. A. Brekken (IEEE Open Access Journal of Power and Energy)
Energy and water systems are deeply interdependent yet organized and managed into separate sectors. Although technological innovations emerge at the intersection of energy and water, these sectors largely operate independently, despite their mutual importance. This persistent challenge is structural, as the sectors are organized and managed as separate systems. More can be done to integrate these sectors for mutual benefit and resilience. This paper provides an overview and a useful categorization of six research areas that bridge the water and energy sectors: integrated planning, integrated operations, data and analytics, policy and economics, hydropower and marine energy, and resilience. The authors lead the IEEE Power & Energy Society Task Force on Water-Power Systems (WPS), which represents an international and rapidly growing collaboration across both energy and water sectors to find common areas of cooperation and innovation. Through the collective efforts of this Task Force, a comprehensive roadmap on water power systems integration was issued in 2023. The paper presents evidence that coordinated efforts in data analytics, policy, and economic interventions can significantly advance hydropower, marine energy, and energy storage technologies, ultimately enhancing the resilience and efficiency of both water and power infrastructures.